Environmental regulation and corporate environmental performance: a bibliometric analysis - Zhang, Yu; Ong, Tze San; Kamarudin, Fakarudin (EnPress Publisher, LLC, 2024)
Under the concept of green development, enterprises will face more environmental constraints. Whether government environmental regulation (ER) can effectively promote corporate environmental performance (CEP) has not yet been unified among scholars, and few studies have conducted bibliometric analysis on ER and CEP. Based on the above, this study has three purposes: first, to fill the research gap by analyzing and visualizing 72 articles on ER and CEP through Biblioshiny and VOSviewer; second, to help scholars easily understand the research development and quickly find promising research directions; and lastly, to enable the government and corporate managers gain a more comprehensive view of ER’s impacts on CEP, which can assist in policy making and business management. The research found that: (a) the number of articles and citations in the field is on the rise. China is the most academically influential country in terms of publications, citations, and collaborations. Journal of Cleaner Production is the top-ranked journal. Ramanathan R, Testa F, and Zhang Y are the top three authors. Environmental management, sustainability, and China are the most popular keywords. Collaboration between authors, institutions, and countries is relatively weak and isolated. (b) ER and CEP have three emerging clusters: Climate Change, FDI, as well as Environmental Awareness, and three core clusters: Environmental Management, Data Envelopment Analysis, and Economic Analysis. The evolution of themes shows a trend from decentralized to centralized and then back to decentralized. (c) Future research can take the Regulatory Framework, Green Technological Innovation, and Environmental Management System as breaking points.